Out-of-hours exercise treadmill testing reduces length of hospital stay for chest pain admissions. Issue 9 (September 2016) - Groarke, John D.; Crean, Peter; Adams, Niamh; Farrell, Terence; Bennett, Kathleen; McMahon, C. Geraldine
Abstract : Aims: The objective was to examine the impact of out-of-hours exercise treadmill tests (ETTs) on length of hospital stay (LOS) for patients admitted to a chest pain assessment unit with symptoms suggestive of acute coronary syndrome. Methods: Prospective observational study with 30-day follow-up of low-to-intermediate-risk chest pain patients undergoing out-of-hours ETT. Eligible patients had a nonischemic ECG, normal 6–12-h ST-segment monitoring, a negative 12-h troponin T assay, and no contraindications to exercise. Observed LOS was compared to expected LOS in the absence of out-of-hours ETT, using Wilcoxon rank-sum test. Estimated bed day savings and major adverse events at 30 days after discharge were examined. Results: Four hundred and twenty-two patients with a mean age of 52 years (SD 13 years, 25–83 years) were evaluated. Fifty-two per cent ( n = 221) were men; 66% ( n = 279) had one or less cardiovascular risk factors; and 79% ( n = 334) of the patients presented on a Friday or Saturday. ETT was performed on a weekend day in 86% ( n = 363) of the patients, facilitating same-day discharges in 71% ( n = 300). The median LOS (interquartile range) was 1 day (1, 2 days) for patients assessed with out-of-hours ETT. The expected median LOS (IQR) was 3 days (2, 4 days) ( P < 0.05) in the absence of out-of-hours ETT. Each out-of-hours ETT was estimated to save a mean (SD, range) of 1.6 (0.6, 1–4) bed days. Thirty-day mortality and readmission rates were 0 and 0.2% (1 of 422), respectively. Conclusion: The availability of out-of-hours ETT facilitates safe early discharge and reduced LOS for low-to-moderate-risk patients admitted with symptoms of acute coronary syndrome.